2015
DOI: 10.1038/ncomms9464
|View full text |Cite
|
Sign up to set email alerts
|

Causal mechanisms and balancing selection inferred from genetic associations with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the most common reproductive disorder in women, yet there is little consensus regarding its aetiology. Here we perform a genome-wide association study of PCOS in up to 5,184 self-reported cases of White European ancestry and 82,759 controls, with follow-up in a further ∼2,000 clinically validated cases and ∼100,000 controls. We identify six signals for PCOS at genome-wide statistical significance (P<5 × 10−8), in/near genes ERBB4/HER4, YAP1, THADA, FSHB, RAD50 and KRR1. Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
276
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(309 citation statements)
references
References 46 publications
27
276
0
6
Order By: Relevance
“…Our data demonstrate that, in particular, extraovarian neuroendocrine AR sites of androgen action are predominantly involved in the pathogenesis of multiple key PCOS characteristics. This provides strong experimental support for recent GWAS findings that highlight the importance of gonadotropin action in the genetic origins of susceptibility to PCOS (24)(25)(26). In concert, these Serum concentrations of dihydrotestosterone, testosterone, dehydroepiandrosterone, 5α-androstane-3α,17β-diol, 5α-androstane-3β,17β-diol, progesterone, luteinizing hormone, and follicle-stimulating hormone.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our data demonstrate that, in particular, extraovarian neuroendocrine AR sites of androgen action are predominantly involved in the pathogenesis of multiple key PCOS characteristics. This provides strong experimental support for recent GWAS findings that highlight the importance of gonadotropin action in the genetic origins of susceptibility to PCOS (24)(25)(26). In concert, these Serum concentrations of dihydrotestosterone, testosterone, dehydroepiandrosterone, 5α-androstane-3α,17β-diol, 5α-androstane-3β,17β-diol, progesterone, luteinizing hormone, and follicle-stimulating hormone.…”
Section: Discussionsupporting
confidence: 57%
“…1). Our findings highlight the importance of extraovarian AR-mediated androgen actions in the origins of PCOS features, which is strongly supported by findings from recent genome-wide association studies (GWAS) of PCOS highlighting the importance of gonadotropins in PCOS (24)(25)(26).…”
supporting
confidence: 67%
“…As noted above, the role of DENND1A splice transcripts in ovarian theca cell steroidogenesis is being investigated. The PCOS susceptibility allele in the FSHB gene is also associated robustly with lower circulating FSH levels [94, 95], and with other phenotypes indicative of diminished ovarian follicle stimulation: later onset of puberty, and lower risk for dizygotic twinning [96]. Together, these genetic findings indicate a co-primary neuroendocrine pathogenesis of PCOS, alongside its likely ovarian etiology.…”
Section: A Pathophysiologymentioning
confidence: 85%
“…The advent of large-scale GWAS with their stringent statistical thresholds has brought robust new insights, although as yet these have been limited to adult PCOS cases and their direct relevance to adolescent PCOS is yet to be established. The first GWAS for PCOS were performed in Han Chinese populations [92, 93]; while the identified genomic loci were replicable in that population, their effects estimates are consistently smaller in Caucasian PCOS cases, possibly due to population differences in genetic architecture or even PCOS sub-phenotypes [94, 95]. …”
Section: A Pathophysiologymentioning
confidence: 99%
“…In mice with neuregulin-ErbB4/2 receptor deficiency the required LHRH failed to be secreted so the sex development of mice was impaired [20]. Day et al reported in their genetic study that ErbB2, ErbB3 and ErbB4 receptors may be associated with PCOS [21]. In another animal study, overexpressed NRG4 has been shown to cause an increase in insulin sensitivity while NRG4 deficiency has been shown to cause insulin resistance.…”
Section: Discussionmentioning
confidence: 92%